The prevalence of aminoglycoside-modifying enzyme genes (aac (6')-I, aac (6')-II, ant (2")-I, aph (3')-VI) in Pseudomonas aeruginosa (Clinics, 2011)
INTRODUCTION: Pseudomonas aeruginosa (P. aeruginosa) is one of the primary opportunistic pathogens responsible for nosocomial infections. Aminoglycosides are an import ant component of antipseudomonal chemotherapy. The inactivation of drugs by modifying enzymes is the most common mechanism of aminoglycoside resistance. OBJECTIVES: The inactivation of aminoglycosides by modifying enzymes is the primary resistance mechanism employed by P. aeruginosa. The aim of the present study was to investigate the occurrence of aminoglycoside resistance and the prevalence of four import ant modifying enzyme genes (aac (6')-I, aac (6')-II, ant (2")-I, aph (3')-VI) in P. aeruginosa in Iran. METHODS: A total of 250 clinical isolates of P. aeruginosa were collected from several hospitals in seven cities in Iran. Antimicrobial susceptibility tests (using the disk diffusion method and E-tests) were performed for all 250 isolates. In addition, all isolates were screened for the presence of modifying enzyme genes by polymerase chain reaction. RESULTS: The resistance rates, as determined by the disk diffusion method, were as follows: gentamicin 43%, tobramycin 38%, and amikacin 24%. Of the genes examined, aac (6')-II (36%) was the most frequently identified gene in phenotypic resist ant isolates, followed by ant (2")-I, aph (3')-VI, and aac (6')-I. CONCLUSIONS: Aminoglycoside resistance in P. aeruginosa remains a signific ant problem in Iran. Therefore, there is considerable local surveillance of aminoglycoside resistance.